Swimming patterns of daphnia magna - Vannessa, Tung (Nanyang Technological University, 2024)
Daphnia, also known as water fleas, are small sized crustaceans that live in different water ecosystems globally, often in lakes and ponds. They are important links in marine food webs because they appear at the bottom of the aquatic food chains as the prey for a multitude of fishes and invertebrates. Daphnids are known to have rapid reproductive capabilities, and are highly selective of their living environment, hence they are commonly used in ecotoxicology and aquatic toxicology experiments. The reactions of different species to diverse kinds of stressors, including pollutants, changes in temperature and pH levels in the waters, allow scientists to gain a better understanding of how contaminants affect aquatic ecosystems. This demonstrates the ecological significance of Daphnia and their research applications as indicators of environmental health, serving as the foundation for advancing knowledge across various fields of study.